Impact of port layouts on inter-terminal-transportation networks - Nicole Nellen; Moritz Poeting; Kristina Bschorer; Carlos Jahn; Uwe Clausen (Data Science in Maritime and City Logistics: Data-driven Solutions for Logistics and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 30, 2020)
Purpose: Major seaports consist of several terminals with different functions. The different locations of terminals in relation to each other influences the organization of inter-terminal transportation as well as transports into the hinterland. The focus of this study is to understand how terminals are arranged in relation to each other to draw conclusions about the effect of the terminal locations on processes and transports. Methodology: The paper provides a comprehensive overview for the locations of terminals and depots within a port. Based on this, a detailed analysis is carried out to develop a classification scheme for ports, which categorizes them according to their geographical characteristics. Findings: Based on the examples of characteristic ports and terminals, we provide findings regarding advantages as well as barriers to transport containers within ports. The aim is to determine the impact of geographical characteristics of ports for handling port-internal traffic. Originality: The existing literature provides an overview of ports and maritime networks, as well as various port concepts. Furthermore, different approaches for the design of container transports between terminals are discussed. However, there is no overview of the geographical location of terminals and depots in ports and their impact on inter-terminal transportation.
urn:nbn:de:gbv:830-882.0115532; hdl:10419/228915; https://econpapers.repec.org/RePEc:zbw:hiclpr:30
Keywords: 650; Logistics; Industry 4.0; Supply Chain Management; Sustainability; City Logistics; Maritime Logistics; Data Science